A Theoretical Study on Rib‐Type Photonic Wires Based on LiNbO3 Thin Film on Insulator. Issue 10 (25th July 2019) - Xu, Qing; Shao, Yan‐Xue; Piao, Rui‐Qi; Chen, Feng; Wang, Xiao; Yang, Xiao‐Fei; Wong, Wing‐Han; Pun, Edwin Yue‐Bun; Zhang, De‐Long
Abstract: A theoretical study on rib‐type photonic wires (PW) based on lithium niobate (LiNbO3 )‐on‐insulator (LNOI) using finite element method is performed. Aiming at 1.55 µm wavelength, effective refractive indices of several lower‐order transverse‐electric/magnetic (TE/TM) modes in the central rib region and the fundamental mode in the slab waveguide in the side region are calculated as a function of geometric parameters of the PW. By comparing effective refractive index of the first‐order mode in the central rib region with that of the fundamental mode in the slab waveguide, single‐mode condition in the central rib region is determined in terms of geometric parameters of the PW. Electric field distributions of fundamental TE and TM modes are also simulated and discussed. In addition, dispersion relation of effective group refractive index of the fundamental mode in the central rib region is calculated and discussed in comparison with those of ridge‐type LNOI PW, traditional Ti‐diffused LiNbO3 strip waveguide, and bulk LiNbO3 single‐crystal. For a fundamental TE mode in a rib‐type LNOI PW with a LiNbO3 film thickness 700 nm, a rib width 1 µm and an etching depth 100–200 nm, nearly zero group index dispersion in the wavelength range 1.31.7 µm can be realized. Abstract : A theoretical study is performed on rib‐type photonic wires (PW) based on LiNbO3 on insulator (LNOI) . Effective index, single‐mode condition, mode‐field and dispersion characteristics of effective group‐index are studied. It is shown that the rib‐type LNOI PW is promising for group‐velocity dispersion engineering, nearly zero group‐index dispersion in the wavelength range 1.3–1.7 µm can be realized for fundamental transverse‐electric mode.